GAPH Survey Forms 431-440 February-March 1981 - Smith, Bartholemew (My University, 1981)
1. 702-710 N. Washington St., Quitman, Georgia 2. 723; 721; 719; N. Washington St., Quitman, Georgia 3. 725 N. Washington St., Quitman, Georgia 4. 803 N. Washington St., Quitman, Georgia 5. 805 N. Washington St., Quitman, Georgia 6. 808 N. Washington St., Quitman, Georgia 7. 811 N. Washington St., Quitman, Georgia 8. 903 N. Washington St., Quitman, Georgia 9. 101 S. Washington St., Quitman, Georgia 10. 209 S. Washington St., Quitman, Georgia
Keywords: Lowndes County Historical Society (Lowndes County, Ga.); Real Property Surveys; Brooks County (Ga.); Quitman (Ga.); Historic Buildings